The Role of Glucose in the Pathogenesis of Alzheimer's Disease Revisited:What Does it Tell us About the Therapeutic use of Lithium? - Strunecka, Anna; Grof, Paul (Central Nervous System Agents in Medicinal Chemistry, 2006)
The ultimate aim of many researchers is to design a drug, which could arrest or delay specifically the clinical evolution of symptoms of Alzheimer's disease (AD). The association of increased activity of glycogen synthase kinase-3 (GSK-3) with neuronal apoptosis, amyloid metabolism, and hyperphosphorylation of protein tau makes this kinase an attractive target for the therapy of neurodegenerative diseases. Lithium has been shown to be an important inhibitor of GSK-3 activity and therefore recently suggested as one of the treatment of AD. For some time, the most widely accepted mechanism of action of lithium was its inhibitory effect on inositol monophosphatase, resulting in depletion of inositol with profound effects on phosphoinositide signaling system. Although much evidence has not supported the inositol depletion hypothesis subsequently, the important role of inositol and inositides in the CNS, in addition to their role in phosphoinositide signaling pathways, has been discussed. A new perspective on the role of glucose in neurodegenerative changes in the CNS has been emerging from several lines of evidence. These accumulated observations may improve our understanding of the links between deficient glucose metabolism in the aging brain and the events leading to the onset of AD. The impairment of glucose utilization might act as the common denominator for the development of pathological hallmarks of AD.
Keywords: protein tau